Snack timing affects tissue clock and metabolic responses in male mice - Begemann, Kimberly; Oster, Henrik (Frontiers in Nutrition, 2022)
Snacking of small quantities of palatable food items throughout the day is common in modern societies and is promoted by 24/7 lifestyles. Long-term mistimed high-caloric food intake disrupts endogenous circadian rhythms and supports the development of obesity and other metabolic disorders. However, less is known about the time-of-day dependent effects of snacking. We hypothesized that already a single snacking episode may affect the circadian regulation of metabolic parameters, in particular when the snack is consumed during the daily rest phase. We performed an acute snack experiment in mice by providing access to chow or chocolate either at day- or nighttime and assessed snack effects on core body temperature, locomotor activity, and gene expression in metabolic tissues. Our results show that daytime chocolate snacking leads to a higher body temperature and locomotor activity increase compared to chow and nighttime intake. This goes along with altered clock and metabolic gene expression in peripheral tissues. Changes in nutrient uptake transporter gene expression in the small intestine suggest increased glucose resorption after daytime snacking. Our results indicate an early mechanism for the adipogenic effect of mistimed high-calorie snacking.